menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
(a/6)-10=(a/3) An equivalent form of this equation is a - 10 = 2a a - 60 = 6a a - 60 = 2a
asked
Mar 9, 2019
231k
views
4
votes
(a/6)-10=(a/3)
An equivalent form of this equation is
a - 10 = 2a
a - 60 = 6a
a - 60 = 2a
Mathematics
college
Mini
asked
by
Mini
7.2k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
we have that
(a/6)-10=(a/3)
(a-60)/6=a/3
3*(a-60)=6*a
(a-60)=(6/3)*a
(a-60)=2*a
the answer is
(a-60)=2*a
alternative method shorter
(a/6)-10=(a/3)
multiply all expression by 6
6*(a/6)-6*10=6*(a/3)
a-60=(6/3)*a
a-60=2*a
Jaybeecave
answered
Mar 14, 2019
by
Jaybeecave
6.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
8.3m
questions
10.9m
answers
Other Questions
What is .725 as a fraction
How do you estimate of 4 5/8 X 1/3
A bathtub is being filled with water. After 3 minutes 4/5 of the tub is full. Assuming the rate is constant, how much longer will it take to fill the tub?
i have a field 60m long and 110 wide going to be paved i ordered 660000000cm cubed of cement how thick must the cement be to cover field
Write words to match the expression. 24- ( 6+3)
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org